DETERMINAN PRODUKSI TANAMAN KOPI ARABIKA DI KECAMATAN MIOMAFFO BARAT KABUPATEN TIMOR TENGAH UTARA - Akoit, Maria Yanti; Sengkoen, Yuliati (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2025)
Timor Tengah Utara Regency is a region in the eastern part of Indonesia that has the potential for growing coffee plants because the climate conditions are suitable for supporting the growth of coffee plants. In addition to chemical inputs, coffee farmers in the district also use organic fertilizers to cultivate Arabica coffee. This study aims to examine the factors that influence Arabica coffee production in Miomaffo Barat Subdistrict, Timor Tengah UtaraRegency. Out of a total population of 127 individuals, 60 Arabica coffee farmers were randomly selected as respondents, accompanied by direct field observations. The Cobb-Douglas production function model was used to analyze the effects of four input variables: land area, organic fertilizer, urea fertilizer, and insecticide. The analysisresults showed that organic fertilizer, urea fertilizer, and insecticide significantly affect Arabica coffee yield per hectare. However, only organic fertilizer contributes positively. In contrast, urea fertilizer and insecticide have negative coefficients. Land area does not show a significant effect and even indicates a negative relationship withcoffee productivity.